Birefringence and Orientation Direction Control of Photoalignable Liquid Crystalline Copolymer Films Based on In Situ Modification of Mesogenic Groups - Uemura, Keigo (Langmuir : the ACS journal of surfaces and colloids, 2024)
Controlling the birefringence of optical films is imperative to fabricate thin birefringent optical devices. Here, new photoalignable liquid crystalline copolymers (PLCPs) with 4-formylphneyl benzoate (PA) and cinnamic acid (CA) side groups are synthesized, which attain high photoreactivity and controllability of the orientation direction. Additionally, the exposed films are treated with 2-aminofluorene (AF) for an in situ condensation of PA with AF to form a Schiff base with a high inherent birefringence. Birefringence of the photoaligned film can be controlled up to 0.45 without disturbing the photoinduced orientation structure